Antifouling nanofiller and preparation method thereof
By grafting natural organic compounds and nanocarrier materials, intelligently responding anti-fouling nanofillers were prepared, which solved the problem of difficult to control the release rate of existing antifouling agents, achieved long-term sterilization and antibacterial effects, and significantly improved the prevention Performance of stain coating.
Patent Information
- Application Number
- CN202411307779.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The release rate of existing antifoulants in the marine environment is difficult to control, resulting in a short coating life and toxic effects on non-target organisms, and it is impossible to achieve long-term and effective environmentally friendly antifouling effects.
Grafted natural organic compounds are used as nanocarrier materials to prepare anti-fouling nanofillers by reacting with nanocarrier materials, combined with anti-fouling bacterializers, and slow release of intelligent responses is achieved, enhancing the bactericidality and antibacteriality of the coating.
It realizes low-cost and environmentally friendly anti-fouling nanofillers, improves the bactericidal and antibacterial properties of the coating, and extends the anti-fouling cycle, significantly improving the anti-fouling effect.
Smart Images

Figure CN119264718A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials and coating materials, and in particular to antifouling nanofillers and preparation methods thereof. Background Art
[0002] With the development of the marine industry, the problem of marine fouling of facilities such as buildings, hulls, pipelines, oil platforms and marine sensors has become increasingly obvious. Marine fouling is mainly caused by the accumulation of marine organisms such as bacteria, algae and barnacles on the surface of underwater facilities. These biological pollutions lead to the continuous accumulation of dirt on the surface of buildings, causing pipeline blockage, increasing the resistance of ships and fuel consumption, and promoting the intensification of corrosion, which will bring huge economic losses and serious problems to the marine industry.
[0003] The most effective and convenient way to prevent marine fouling is through coatings that release toxic bactericidal molecules at a controlled rate. Traditional antifouling coatings mainly rely on compounds containing heavy metals (such as copper and tin), which inhibit biofouling by slowly releasing toxic substances. However, these toxic substances can cause serious pollution to marine ecosystems and have toxic effects on non-target organisms. Therefore, it is extremely important to develop long-term, effective, and environmentally friendly antifouling agents.
[0004] At present, since antifouling agents are usually physically mixed into the coating, their release rate is difficult to control, resulting in a short life of the coating. Nanomaterials can be used to encapsulate antifouling agents that hydrolyze or rupture under external stimuli to control the release of the antifouling agents. However, directly encapsulating fungicides into nanomaterials cannot guarantee the effective load of antifouling fungicides and cannot guarantee that they have long-lasting fungicidal properties. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present disclosure provides an antifouling nanofiller and a preparation method thereof.
[0006] The antifouling nanofiller disclosed in the present invention comprises raw materials including nanocarrier materials and antifouling bactericides; the characteristic is that the nanocarrier materials comprise nanocarrier materials grafted with natural organic compounds, and the natural organic compounds comprise at least one of natural antibacterial alcohol or phenol compounds and their derivatives.
[0007] In some embodiments, the natural organic compound includes at least one of 7-hydroxy-4-methylcoumarin, catechin, resveratrol, and lavandulol.
[0008] The preparation method of the antifouling nanofiller disclosed in the present invention comprises steps 1 to 4: step 1: purifying the nanocarrier material; step 2: modifying the purified nanocarrier material; step 3: grafting the modified purified nanocarrier material with a natural organic compound; step 4: loading the antifouling bactericide on the product obtained in step 3 to prepare the antifouling nanofiller; wherein the natural organic compound comprises at least one of natural antibacterial alcohol or phenolic compounds and their derivatives.
[0009] In some embodiments, the natural organic compound includes at least one of 7-hydroxy-4-methylcoumarin, catechin, resveratrol, and lavandulol.
[0010] In some embodiments, in step 1, the purified nanocarrier material is obtained by reacting substances including halloysite nanotubes, deionized water, and sodium hexametaphosphate.
[0011] In some embodiments, step 1 is: dispersing the nanocarrier material in deionized water to form a dispersion 1, adding sodium hexametaphosphate to the dispersion 1, adjusting the pH value of the dispersion 1 to 8-11, stirring the reaction for 12-24 hours; then standing for 4-8 hours; then centrifuging to obtain the upper clear liquid; then further centrifuging to obtain the upper solution until the solution is neutral, and freeze-drying to obtain a solid precipitate, which is the purified nanocarrier material.
[0012] In some embodiments, in step 2, the modification process is obtained by reacting materials including purified halloysite nanotubes, 3-aminopropyltriethoxysilane, dimethyl sulfoxide, and succinic anhydride in an organic solvent.
[0013] In some embodiments, step 2 is: dispersing the purified nanocarrier material in anhydrous toluene to form a mixture 1, degassing the mixture 1 with argon for 40 to 60 minutes; adding a silane coupling agent to the mixture 1 to form a mixture 2, stirring and refluxing the mixture 2 in an argon atmosphere at 100 to 120° C. for 12 to 24 hours to obtain a mixture 3; centrifuging and drying the mixture 3 to obtain a precipitate; dispersing the precipitate in dimethyl sulfoxide, then adding succinic anhydride and triethylamine, stirring at 40 to 80° C. for 48 to 60 hours, and centrifuging to obtain a modified product.
[0014] In some embodiments, step 3 is: adding butyl acetate, modified nanocarrier material grafting, and natural organic compounds into a three-necked flask, filling the three-necked flask with nitrogen to keep the reaction in a nitrogen environment, reflux stirring the reaction at 60-100°C for 12-24h, and then precipitating in cold ethanol to obtain a grafted product.
[0015] In some embodiments, step 4 is: adding the grafted product obtained in step 3, antifouling bactericide, ethanol, anhydrous toluene, oleic acid, and oleylamine into a container to form a mixture, then adding ascorbic acid, stirring continuously at 50-80°C for 30-60 minutes to obtain a dark solution, and obtaining the antifouling nanofiller by centrifugation, washing, and drying.
[0016] The present disclosure includes at least the following beneficial effects: first, the raw material cost is low and it is green and environmentally friendly; second, the antifouling nanofiller prepared by the method described in the present disclosure has a good intelligent response effect, while improving the antifouling effect of the loaded antifouling agent; third, when applied to a coating, the bactericidal and antibacterial properties of the coating can be enhanced, and the antifouling cycle can be improved, highlighting its antifouling advantage. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The infrared spectra of different products in the preparation process of Example 1 are shown in FIG.
[0018] Figure 2 The UV-visible absorption spectra of different products in the preparation process of Example 1 are shown.
[0019] Figure 3 This is a graph showing the particle sizes of different products during the preparation process of Example 1.
[0020] Figure 4 This is the Zeta potential diagram of different products in the preparation process of Example 1.
[0021] Figure 5 This is an experimental diagram of the antibacterial effect of different products in the preparation process of Example 1.
[0022] Figure 6 This is the SEM image of the HTHA product prepared in Example 1.
[0023] Figure 7 This is the SEM image of the antifouling nanofiller product prepared in existing literature.
[0024] Figure 8 The long-acting UV-visible absorption spectra of different products in the preparation process of Example 1; wherein d0, d3, d13, d21, and d28 represent the curves on day 0, day 3, day 12, day 21, and day 28, respectively. DETAILED DESCRIPTION
[0025] It should be understood that the disclosed embodiments are only examples, and the present disclosure can be implemented in various forms. Therefore, the specific details of the present disclosure should not be interpreted as limitations, but only as the basis for the claims, to teach those of ordinary skill in the art to implement the present disclosure in various ways. In the description of the present disclosure, the terms and professional terms that are not clearly stated are common knowledge of those skilled in the art, and the methods that are not clearly stated are conventional methods known to those skilled in the art. In the description of the present disclosure, the term "grafting" is the combination of substances in chemistry, including but not limited to all objectively combined forms such as complexation, bonding, and growth.
[0026] The endpoints of the ranges and any values disclosed in the present disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be deemed to be specifically disclosed herein.
[0027] Next, the antifouling nanofiller disclosed in the present invention and the preparation method thereof are described.
[0028] The main concept of the present disclosure is: natural organic compounds are used as modifiers to react with carboxylated nano-carrier materials to obtain antifouling nano-fillers. The antifouling nano-fillers not only have the advantages of broad bactericidal activity, low toxicity, and diverse antibacterial mechanisms, but also have the function of intelligent response, using the water environment as a stimulation factor to promote the slow and intelligent release of the bactericide, thereby achieving a long-term and effective bactericidal effect.
[0029] [Antifouling Nanofiller]
[0030] The antifouling nanofiller disclosed in the present invention comprises raw materials including nanocarrier materials and antifouling bactericides; the characteristic is that the nanocarrier materials comprise nanocarrier materials grafted with natural organic compounds, and the natural organic compounds comprise at least one of natural antibacterial alcohol or phenol compounds and their derivatives.
[0031] In some embodiments, the natural organic compound includes at least one of 7-hydroxy-4-methylcoumarin, catechin, resveratrol, and lavandulol.
[0032] In some embodiments, the antifouling bactericide comprises at least one of metal nitrates, metal chlorides, and metal oxides. In some embodiments, the antifouling bactericide comprises at least one of silver nitrate, copper chloride, copper sulfate, and zinc sulfate.
[0033] In some embodiments, the nanocarrier material includes at least one of a tubular nanocarrier material, a sheet nanocarrier material, and a spherical nanocarrier material. In some embodiments, the nanocarrier material includes a natural nanomaterial. In some embodiments, the natural nanomaterial includes at least one of nano-silicon dioxide, halloysite nanotubes, and nano-titanium dioxide, preferably halloysite nanotubes. Halloysite nanotubes are a tubular aluminosilicate clay with good biocompatibility and environmental friendliness. They will not cause serious pollution to the environment and are a sustainable antifoulant carrier option. At the same time, they have a unique hollow structure and a high specific surface area, which enables them to effectively adsorb and load antifoulants, improve the stability and release efficiency of antifoulants, and use them as antifoulant carriers to achieve slow release of antifoulants and extend the service life of antifouling fillers. At the same time, due to the chemical composition of its inner and outer surfaces, after modification and modification, flexible design and application solutions can be provided to improve the antifoulant loading effect.
[0034] In some embodiments, for the tubular nanocarrier material, the organic compound is grafted to the inner wall and / or outer wall of the tubular nanocarrier material. In some embodiments, for the sheet-like nanocarrier material, the organic compound is grafted to at least one side of the sheet-like nanocarrier material. In some embodiments, for the spherical nanocarrier material, the organic compound is grafted to the inner side and / or outer side of the spherical nanocarrier material.
[0035] [Preparation method of antifouling nanofiller]
[0036] The method for preparing the antifouling nanofiller disclosed in the present invention comprises steps 1 to 4:
[0037] Step 1: purify the nanocarrier material; Step 2: modify the purified nanocarrier material; Step 3: graft the modified purified nanocarrier material with a natural organic compound; Step 4: load the product obtained in step 3 with an antifouling bactericide to obtain an antifouling nanofiller; wherein the natural organic compound includes at least one of natural antibacterial alcohol or phenolic compounds and their derivatives.
[0038] In some embodiments, in step 1, the nano-carrier material comprises at least one of nano-silicon dioxide, halloysite nanotubes, and nano-titanium dioxide, preferably halloysite nanotubes.
[0039] In some embodiments, in step 1, the purified nanocarrier material is obtained by reacting substances including halloysite nanotubes, deionized water, and sodium hexametaphosphate.
[0040] In some embodiments, step 1 is: dispersing the nanocarrier material in deionized water to form a dispersion 1, adding sodium hexametaphosphate to the dispersion 1, adjusting the pH value of the dispersion 1 to 8-11, stirring the reaction for 12-24 hours; then standing for 4-8 hours; then centrifuging to obtain the upper clear liquid; then further centrifuging to obtain the upper solution until the solution is neutral, and freeze-drying to obtain a solid precipitate, which is the purified nanocarrier material.
[0041] In some embodiments, in step 2, the modification process is obtained by reacting materials including purified halloysite nanotubes, 3-aminopropyltriethoxysilane, dimethyl sulfoxide, and succinic anhydride in an organic solvent.
[0042] In some embodiments, step 2 is: dispersing the purified nanocarrier material in anhydrous toluene to form a mixture 1, degassing the mixture 1 with argon for 40 to 60 minutes; adding a silane coupling agent to the mixture 1 to form a mixture 2, stirring the mixture 2 at 100 to 120° C. in an argon atmosphere and reflux for 12 to 24 hours to obtain a mixture 3; centrifuging and drying the mixture 3 to obtain a precipitate; dispersing the precipitate in dimethyl sulfoxide, then adding succinic anhydride and triethylamine, stirring at 40 to 80° C. for 48 to 60 hours, and centrifuging to obtain a modified product. In some embodiments, the silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane.
[0043] In some embodiments, in step 3, the natural organic compound includes at least one of 7-hydroxy-4-methylcoumarin, catechin, resveratrol, and lavandulol.
[0044] In some embodiments, step 3 is: adding butyl acetate, modified nanocarrier material grafting, and natural organic compounds into a three-necked flask, filling the three-necked flask with nitrogen to keep the reaction in a nitrogen environment, reflux stirring the reaction at 60-100°C for 12-24h, and then precipitating in cold ethanol to obtain a grafted product.
[0045] In some embodiments, in step 4, the antifouling fungicide comprises at least one of metal nitrates, metal chlorides, and metal oxides. In some embodiments, in step 4, the antifouling fungicide comprises at least one of silver nitrate, copper chloride, copper sulfate, and zinc sulfate.
[0046] In some embodiments, step 4 is: adding the grafted product obtained in step 3, antifouling bactericide, ethanol, anhydrous toluene, oleic acid, and oleylamine into a container to form a mixture, then adding ascorbic acid, stirring continuously at 50-80°C for 30-60 minutes to obtain a dark solution, and obtaining the antifouling nanofiller by centrifugation, washing, and drying.
[0047] [Example]
[0048] The present disclosure is further described below in conjunction with the examples. In the following examples and comparative examples, the reagents, materials and instruments used, unless otherwise specified, can be obtained commercially or prepared by methods known in the art.
[0049] Example 1
[0050] Step 1: Weigh 100g of halloysite nanotubes in a 500mL beaker, add 300mL of deionized water, and stir mechanically for 1h; add 10g of sodium hexametaphosphate, adjust the pH value of the solution in the beaker to 8 with 10wt% sodium hydroxide solution, and continue stirring for 12h. After standing for 4h, take the upper solution and centrifuge (4000rpm, 15min); obtain the upper clear liquid and centrifuge (10000rpm, 25min). Get the solid precipitate and wash it with deionized water (10000rpm, 25min) 5 times. Take the solid precipitate, place it in a vacuum freeze dryer for vacuum drying, and then obtain the purified halloysite nanotubes (referred to as HNTs).
[0051] Step 2: The crushed HNTs (1.5 g) were dispersed in anhydrous toluene (15 mL), and the solution was degassed with argon for 40 min. 1.5 mL of silane coupling agent was added to the mixture, and the resulting mixture was stirred and refluxed at 120 ° C in an argon atmosphere for 12 h. The mixture was then centrifuged at 8000 rpm for 10 min, and the precipitate was repeatedly washed with anhydrous toluene to remove the ungrafted coupling agent. Finally, it was dried in a vacuum oven at 50 ° C for 24 h, and the resulting product was dispersed in dimethyl sulfoxide (5 mL). Then succinic anhydride (200 mg) and triethylamine (200 mg) were added to the mixed solution, stirred at 40 ° C for 48 h, centrifuged to obtain a product named HTC, and washed 3 times with ethanol.
[0052] Step 3: First, add 10 g of butyl acetate, 1 g of HTC and 1 g of 7-hydroxy-4-methylcoumarin into a round-bottom flask filled with nitrogen. The reaction solution is refluxed and stirred at 70°C for 12 h, and then precipitated in cold ethanol. The product is named HTCH.
[0053] Step 4: HTCH (30 mg), AgNO3 (44 mg), ethanol (5 mL), anhydrous toluene (5 mL), oleic acid (OAc, 0.4 mL) and oleylamine (OAm, 0.4 mL) were added to a 250 mL single-necked flask and ultrasonically treated for 2 min. After the resulting mixture was stirred at 55 ° C for 1 min, 100 mg of ascorbic acid was added, and the mixture was continuously stirred at 55 ° C for 25 min to obtain a dark solution. Then, the mixture was centrifuged at 8000 rpm for 10 min. The precipitate was repeatedly washed with anhydrous ethanol / anhydrous toluene solution (volume ratio of 1:1) and dried in a vacuum oven at 30 ° C for 24 h. The resulting powder product was an antifouling nanofiller named HTHA.
[0054] Embodiment 2-5
[0055] The preparation method of Example 2-5 is the same as that of Example 1, except that the contents of halloysite nanotubes and sodium hexametaphosphate in step 1 of Example 2-5 are different, see Table 1 for details.
[0056] Example 6
[0057] Step 1: Weigh 250g of halloysite nanotubes into a 500mL beaker, add 400mL of deionized water, and stir mechanically for 1h; add 3g of sodium hexametaphosphate, adjust the pH value of the solution in the beaker to 9 with 10wt% sodium hydroxide solution, and continue stirring for 12h. After standing for 4h, take the upper solution and centrifuge (3000rpm, 15min); obtain the upper clear liquid and centrifuge (8000rpm, 25min). Get the solid precipitate and wash it with deionized water (8000rpm, 25min) 5 times. Take the solid precipitate, place it in a vacuum freeze dryer for vacuum drying, and then obtain the purified halloysite nanotubes, which are recorded as HNTs.
[0058] Step 2: The crushed HNTs (1.5 g) were dispersed in anhydrous toluene (15 mL), and the solution was degassed with argon for 40 min. 1.5 mL of 3-aminopropyltriethoxysilane was added to the mixture, and the resulting mixture was stirred and refluxed at 120 ° C in an argon atmosphere for 12 h. The mixture was then centrifuged at 8000 rpm for 10 min, and the precipitate was repeatedly washed with anhydrous toluene to remove ungrafted APTES. Finally, it was dried at 50 ° C in a vacuum oven for 24 h, and the resulting product was dispersed in dimethyl sulfoxide (5 mL). Then succinic anhydride (200 mg) and triethylamine (200 mg) were added to the mixed solution, stirred at 40 ° C for 48 h, centrifuged to obtain a product named HTC, and washed 3 times with ethanol.
[0059] Step 3: First, add 10 g butyl acetate, 10 g HTC and 1.36 g 7-hydroxy-4-methylcoumarin into a round-bottom flask filled with nitrogen. The reaction solution is refluxed and stirred at 70°C for 12 h, and then the product is precipitated in cold ethanol and named HTCH.
[0060] Step 4: HTCH (30 mg), AgNO3 (44 mg), ethanol (5 mL), anhydrous toluene (5 mL), oleic acid (OAc, 0.4 mL) and oleylamine (OAm, 0.4 mL) were added to a 250 mL single-necked flask and ultrasonically treated for 2 min. After the resulting mixture was stirred at 55 ° C for 1 min, 100 mg of ascorbic acid was added, and the mixture was continuously stirred at 55 ° C for 25 min to obtain a dark solution. Then, the mixture was centrifuged at 8000 rpm for 10 min. The precipitate was repeatedly washed with anhydrous ethanol / anhydrous toluene (volume ratio of 1:1) solution and dried in a vacuum oven at 30 ° C for 24 h. The resulting powder product was an antifouling nanofiller named HTHA.
[0061] Examples 7-10
[0062] The preparation method of Examples 7-10 is the same as that of Example 6, except that the contents of HNTs, silane coupling agent, HTC, 7-hydroxy-4-methylcoumarin, HTCH, and silver chloride in Step 3, Step 4, and Step 5 of Examples 7-10 are different, see Table 1 for details.
[0063] The material parameters involved in Examples 1-10 are shown in Table 1. For ease of explanation, symbols are used in Table 1 to represent specific materials:
[0064] A1: halloysite nanotubes;
[0065] A2: Sodium hexametaphosphate;
[0066] B1: HNTs;
[0067] B2: silane coupling agent;
[0068] B3:HTC;
[0069] B4: 7-hydroxy-4-methylcoumarin;
[0070] B5:HTCH.
[0071] The relevant products in the process of Example 1 were respectively tested by infrared, ultraviolet, particle size, Zeta potential, antibacterial, SEM, and long-term ultraviolet-visible absorption spectrum. The results are as follows: Figure 1-8 shown.
[0072] Table 1 Material parameters in Examples 1-10
[0073] A1 / g A2 / g B1 / g B2 / g B3 / g B4 / g B5 / g B6 / g Example 1 100 10 1.5 1.5 1 1 0.03 0.044 Example 2 200 5 1.5 1.5 1 1 0.03 0.044 Example 3 250 3 1.5 1.5 1 1 0.03 0.044 Example 4 200 2 1.5 1.5 1 1 0.03 0.044 Example 5 150 1 1.5 1.5 1 1 0.03 0.044 Example 6 250 3 2 4 10 1 0.06 0.088 Example 7 250 3 1.5 3 10 1.5 0.06 0.06 Example 8 250 3 1 2 10 0.5 0.12 0.1 Example 9 250 3 1.5 1.5 10 2 0.15 0.25 Example 10 250 3 2 2 10 2.5 0.3 0.44
[0074] Figure 1-5 They are the infrared, ultraviolet, particle size and Zeta point test and antibacterial test diagrams of HNTs, HTCB and HTBC in Example 1. In the infrared spectrum of 7-hydroxy-4-methylcoumarin, 3128 cm -1 、1678cm -1 、1598cm -1 The characteristic peak at 1637 cm is attributed to the OH hydrogen bond between the hydroxyl stretching vibration and the CH stretching vibration of the aromatic ring. -1 The asymmetric stretching vibration peak appears at , indicating that 7-hydroxy-4-methylcoumarin has been successfully introduced into HTCH. In the UV-visible absorption spectrum of HTCH, the presence of the characteristic peak of 7-hydroxy-4-methylcoumarin can also explain the successful preparation of HTCH. At the same time, the peak value is obtained in the UV-visible absorption spectrum at d3 test and tends to be stable at d13. In the subsequent test until d28, the peak value still has a slow upward trend, which can explain the long-term release of the bactericidal agent. The increase in the Zeta potential of HNTs to the Zeta potential of HTCH and the change in particle size from HNTs to HTCB can prove the successful preparation of HTCH. In addition, after experiments and tests, the infrared, ultraviolet, particle size and Zeta potential test diagrams of the products prepared in Examples 2-10 can all illustrate the successful preparation of the relevant products.
[0075] Figure 5 The figure shows the bacterial growth in the culture medium with Bacillus and Pseudoalteromonas added to HTCH and HTHA in Example 1. In the control group, the solid culture medium was covered with a large number of two bacterial colonies. The number of bacteria in the HTCH solid culture medium was relatively small compared with the blank group, while the number of bacteria in the HTHA solid culture medium was greatly reduced compared with the blank group, indicating the effective load of the antifouling bactericide. After being placed for another 24 hours, sampling and observation revealed that there was still no obvious bacterial colony in the HTCH solid culture medium. Therefore, the HTHA antifouling nanofiller finally prepared in this example has an excellent bactericidal effect.
[0076] The HTHA powder of Example 1 was placed under a SEM electron microscope for observation. The results are as follows: Figure 6 As shown, compared with the antifouling nanofiller obtained in the existing literature (Deng Yajun. Preparation and performance study of composite anticorrosion and antifouling organic coating [D]. Xiamen University, 2022. DOI: 10.27424 / d.cnki.gxmdu.2022.000119.), the bactericide loading amount of the HTHA powder in Example 1 is significantly improved compared with the bactericide loading amount of the product in the existing literature.
[0077] The ethanol solution of HTCH in Example 1 was subjected to UV tests on days 0, 1, 3, 7, 13, 21 and 28. The results are as follows: Figure 8 As shown, on the 28th day, it can still be found that the curve has a clear upward trend, proving the long-term effectiveness of its intelligent response bactericidal function.
[0078] In summary, the antifouling nanofiller provided by the present disclosure has low raw material cost and is green and environmentally friendly; organic compounds are grafted onto natural nanomaterials to give them long-lasting bactericidal properties, and bactericides are loaded to further increase their bactericidal ability.
[0079] The above description is only an example of the present disclosure and does not constitute any form of limitation to the present disclosure. Although the present disclosure is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present disclosure. Any technician familiar with the profession, without departing from the scope of the technical solution of the present disclosure, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution of the present disclosure.
Claims
1. An antifouling nanofiller, whose raw materials include nano carrier materials and antifouling bactericides; characterized in that: The nano-carrier material comprises a nano-carrier material grafted with a natural organic compound, wherein the natural organic compound comprises at least one of natural antibacterial alcohol or phenol compounds and derivatives thereof.
2. The antifouling nanofiller according to claim 1, characterized in that: The natural organic compound includes at least one of 7-hydroxy-4-methylcoumarin, catechin, resveratrol and lavandulol.
3. A method for preparing an antifouling nanofiller, characterized in that: Includes steps 1 to 4: Step 1: Purification of nanocarrier material; Step 2: Modifying the purified nanocarrier material; Step 3: grafting the modified purified nanocarrier material with a natural organic compound; Step 4: Load the antifouling bactericide on the product obtained in step 3 to prepare an antifouling nanofiller; Wherein, the natural organic compound includes at least one of natural antibacterial alcohol or phenol compounds and their derivatives.
4. The method for preparing the antifouling nanofiller according to claim 3, characterized in that: The natural organic compound includes at least one of 7-hydroxy-4-methylcoumarin, catechin, resveratrol and lavandulol.
5. The method for preparing the antifouling nanofiller according to claim 1, characterized in that: In step 1, the purified nanocarrier material is obtained by reacting substances including halloysite nanotubes, deionized water, and sodium hexametaphosphate.
6. The method for preparing the antifouling nanofiller according to claim 1, characterized in that: The step 1 is as follows: dispersing the nano-carrier material in deionized water to form a dispersion 1, adding sodium hexametaphosphate to the dispersion 1, adjusting the pH value of the dispersion 1 to 8-11, stirring the reaction for 12-24 hours; then standing for 4-8 hours; then centrifuging to obtain the upper clear liquid; then further centrifuging to obtain the upper solution until the solution is neutral, and freeze-drying to obtain a solid precipitate, which is the purified nano-carrier material.
7. The method for preparing the antifouling nanofiller according to claim 1, characterized in that: In step 2, the modification process is obtained by reacting materials including purified halloysite nanotubes, 3-aminopropyltriethoxysilane, dimethyl sulfoxide, and succinic anhydride in an organic solvent.
8. The method for preparing the antifouling nanofiller according to claim 1, characterized in that: The step 2 comprises: dispersing the purified nano-carrier material in anhydrous toluene to form a mixture 1, degassing the mixture 1 with argon for 40 to 60 minutes; adding a silane coupling agent to the mixture 1 to form a mixture 2, stirring and refluxing the mixture 2 in an argon atmosphere at 100 to 120° C. for 12 to 24 hours to obtain a mixture 3; centrifuging and drying the mixture 3 to obtain a precipitate; dispersing the precipitate in dimethyl sulfoxide, then adding succinic anhydride and triethylamine, stirring at 40 to 80° C. for 48 to 60 hours, and centrifuging to obtain a modified product.
9. The method for preparing the antifouling nanofiller according to claim 1, characterized in that: The step 3 is: adding butyl acetate, the modified nano-carrier material graft, and the natural organic compound into a three-necked flask, filling the three-necked flask with nitrogen to keep the reaction in a nitrogen environment, refluxing and stirring the reaction at 60-100° C. for 12-24 hours, and then precipitating in cold ethanol to obtain a grafted product.
10. The method for preparing the antifouling nanofiller according to claim 1, characterized in that: The step 4 comprises: adding the grafted product obtained in step 3, the antifouling bactericide, ethanol, anhydrous toluene, oleic acid and oleylamine into a container to form a mixture, then adding ascorbic acid, stirring continuously at 50 to 80° C. for 30 to 60 minutes to obtain a dark solution, and obtaining the antifouling nanofiller by centrifugation, washing and drying.
Citation Information
Patent Citations
Organic silicon antifouling coating and preparation method thereof
CN115074008A
Magnetically-driven high-dispersion self-repairing coating as well as preparation method and application thereof on underwater metal surface
CN117285862A
Antifouling nanofiller and preparation method thereof
CN118222129A
Antifouling coating material
JP2001114616A
Cited By
High-water-absorption fiber for paper diaper and preparation method of high-water-absorption fiber
CN120060995A